2016
DOI: 10.1007/s12010-016-2238-x
|View full text |Cite
|
Sign up to set email alerts
|

A Phenylurea Cytokinin, CPPU, Elevated Reducing Sugar and Correlated to Andrographolide Contents in Leaves of Andrographis paniculata (Burm. F.) Wall. Ex Nees

Abstract: Cytokinins are phytohormones that play multiple roles to control plant growth and development. In this study, leaf biomass and the production of andrographolide compounds in a medicinal plant Andrographis paniculata were significantly increased after exogenously treating with the synthetic cytokinin cytokinin-1-(2-chloro-4-pyridyl)-3-phenylurea (CPPU) at 0 (water), 5, or 10 mg L and observed the results for 24 h, 48 h, and 7 days of treatment. It was found that CPPU could significantly enhance new axillary bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recent findings posit the role of cytokinins (CKs) in mediating cellular responses to drought acclimation [4]. Exogenous application of cytokinins improves plant soluble sugar contents which in turn act as osmolytes to help plants tolerate osmotic stresses [5]. Moreover, CKs play a crucial role in delaying senescence, reducing oxidative damage and upholding plant growth under osmotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings posit the role of cytokinins (CKs) in mediating cellular responses to drought acclimation [4]. Exogenous application of cytokinins improves plant soluble sugar contents which in turn act as osmolytes to help plants tolerate osmotic stresses [5]. Moreover, CKs play a crucial role in delaying senescence, reducing oxidative damage and upholding plant growth under osmotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins are broadly classified as either purine-type or phenyl-urea-type and we tested one of each, benzyl-aminopurine (BA) and 4PU-30, respectively, both synthetic. Phenyl-urea cytokinins are of interest because of their chemical stability and independence of nucleotide metabolism ( Worakan et al, 2017 ). Either of these cytokinins modestly promoted cotyledon expansion.…”
Section: Resultsmentioning
confidence: 99%
“…CPPU (N-2-(chloro-4-pyridyl)-N-phenyl urea), a phenyl-urea-based synthetic cytokinin, is a competitive inhibitor of cytokinin oxidase/dehydrogenase (CKX) that helps the plants to retain enhanced cytokinin concentration (Kopečný et al 2010;Nisler et al 2016). The previous studies of our laboratory indicated the positive impact of cytokinin spray (at 5 mg⋅L −1 CPPU) on the process of photosynthesis in rice under drought stress (Gujjar et al 2020), the contents of soluble sugars in a medicinal plant, Andrographis paniculata (Worakan et al 2017), and the adaptability of rice to salinity stress (Gashaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%